Design of an Automatic Gate Barrier Based on Quick Response Code at Sultan Ageng Tirtayasa University Campus - Henriana Henriana; Didik Aribowo; Irwanto Irwanto (Journal of Engineering, Electrical and Informatics, 2026)
This research presents the design and implementation of an automatic gate barrier system based on Quick Response (QR) Code, integrated with Optical Character Recognition (OCR) technology for vehicle license plate verification. The system is controlled by an ESP32 microcontroller connected to a web server, enabling real-time data verification through the Internet of Things (IoT) network. The study applies the Waterfall development model, including system requirements analysis, hardware and software design, and comprehensive testing stages. Testing with 54 vehicle data samples showed that the system achieved a 70% success rate in validating both QR Code and license plate data, while 30% failed due to insufficient lighting and improper camera positioning. These results demonstrate that the system significantly improves security, efficiency, and organization of parking management, especially within university environments. The integration of QR Code and OCR technologies provides an effective solution for IoT-based automatic parking systems, enhancing both convenience and reliability for users.